تقييم دقة قيم الهبوطات، عند تحديد التشوهات الشاقولية - القاموع, أديب محمود (Latakia University Journal -Engineering Sciences Series, 2019)
إن المنشآت الهندسية المختلفة، تتعرض خلال فترة التنفيذ وطيلة فترة الاستثمار، بشكل عام، إلى تشوهات أفقية وشاقولية. تم التركيز في هذا البحث على دراسة وتحليل مفهوم تقييم دقة تحديد قيم الهبوطات الشاقولية فقط. وذلك عند دراسة التشوهات في المنشآت الهندسية. وتم تحديد الأخطاء المتوسطة التربيع لقيم الهبوطات الشاقولية ، عند دراسة الشوهات الشاقولية، باستخدام طريقتين مختلفتين، هما: الطريقة الأولى: استخدمت فيها علاقة الخطأ المتوسط التربيع لتابع المتحولات المترابطة. وفي الطريقة الثانية تم من خلال استخدام مصفوفة معاملات الارتباط ومصفوفة أمثال الأوزان. وخلص البحث إلى توصيات منها: ضرورة استخدام التسوية الهندسية الدقيقة لإجراء قياسات التسوية لتحديد التشوهات الشاقولية. واستنتاج أن الطريقة الأولى هي الأفضل للحصول على النتائج المطلوبة في دراسة التشوهات الشاقولية للمنشأ الهندسي. The different engineering projects are exposed to horizontal and vertical deformations during the period of execution and exploitation. The research focused on studying and analyzing the evaluation of the accuracy of vertical settlements values only during our study of deformations of engineering projects. It determined the average square errors of vertical settlements values, while studying vertical deformations. Two different ways were determined: The first way is by using the formula for the average square error of the function of correlated arguments. The second way is by deducting the matrix of coefficient of correlation and weight matrix. The research has recommendations that precise leveling must be used to measure the leveling for determining the vertical deformations. The first way is better to obtain the results of vertical deformations for engineering projects.